Becoming an Effective Shadow Teacher: Characteristics, Skills, and Strategies - Aiyuda, Nurul; Hafizah, Nasywa; Fitria, Nengsi (KnE Social Sciences, 2025)
Shadow teachers, or additional educators, play a crucial role in inclusive education by supporting students with special needs. This study explores the characteristics, skills, and strategies required for shadow teachers to be effective educators. A literature review was conducted, searching relevant databases with keywords such as “effective shadow teacher,” “good shadow teacher,” and “strategic shadow teacher.” The search was broadened with terms like “special needs” and “inclusive,” identifying 10 articles published between 2014 and 2024. The analyzed articles highlight several essential attributes for shadow teachers, including patience, empathy, and a commitment to ongoing learning. Critical skills identified include effective communication, behaviour management, and adapting teaching methods to students’ learning styles. Effective practice involves providing personalized support, using positive reinforcement, and regularly assessing and adjusting teaching methods to meet each student’s progress and unique needs. This review offers practical recommendations for educators and policymakers to improve support systems in inclusive education.